The butcher's wife - Hughes, Terry; Nicita, Wally; Lloyd, Lauren; Litwak, Ezra; Schwartz, Marjorie; Moore, Demi; Daniels, Jeff, 1955-; Dzundza, George; McDormand, Frances; Colin, Margaret, 1958-; Steenburgen, Mary; Paramount Pictures Corporation; et al. (Hollywood, Calif. : Paramount Home Video, 2001)
A clairvoyant misinterprets signs she believes are leading her to her soulmate, but the error eventually does lead her to true love.
Title from container.
Originally released as a motion picture in 1991.
Special features include: interactive menus ; scene selection ; theatrical trailer.
Music by Michael Gore ; director of photography, Frank Tidy.
Demi Moore, Jeff Daniels, George Dzundza, Frances McDormand, Margaret Colin, Mary Steenburgen.
MPAA rating: PG-13.
Keywords: Butchers -- Drama; Clairvoyants -- Drama; Comedy films; Feature films; French language materials -- Bilingual; Romantic comedy films